Heterogeneous rheology controlled postseismic deformation of the 2011 Tohoku‐Oki earthquake - Jun Muto; Bunichiro Shibazaki; Takeshi Iinuma; Yoshihiro Ito; Yusaku Ohta; Satoshi Miura; Yoshihiko Nakai (Geophysical Research Letters)
Abstract Using two‐dimensional finite element modeling, we reproduced the observed postseismic deformation of the 2011 Tohoku‐Oki earthquake. Our model, which accounts for the lithosphere‐asthenosphere boundary and weak zones beneath volcanoes, was able to reproduce small‐scale (<20 km) perturbations in postseismic deformation observed by the dense geodetic network, such as local subsidence around Quaternary volcanoes. The inverted afterslip has a peak at the downdip limit of the main rupture region on the subducting plate interface, consistent with physical predictions. The combination of afterslip and viscoelastic relaxation in a heterogeneous rheology model explains the observations well, even on small scales.